A SURVEY ON ANESTHESIA MANAGEMENT PRACTICE BY SMALL ANIMAL VETERINARIAN IN DKI JAKARTA AND WEST JAVA PROVINCES - Khalifah, Hadid; Soehartono, Raden Harry; Siswandi, Riki (Universitas Syiah Kuala, 2024)
his study was designated to the members of the Indonesian Veterinary Medical Association (IVMA) in DKI Jakarta and West Java Province between May and August 2023. The sample size was calculated with the Slovin method which covered 260 respondents with a significance level of 5.4%. Questions was focused mainly on the respondents identity, perianesthesia procedures, and anesthesia topic for continuing professional development. The majority of respondents performed 5 cases of anesthesia per week in dogs (76.9%) and cats (36.2%). Preanesthesia physical examination was carried out by 96% of respondents. Premedication was always given to dogs (66.2%) and cats (63.5%). IV catheter placement was always given in 41.2% of dogs and frequently in 38.5% of cats. Atropine was the most widely used premedication agent (88%) and meloxicam mainly used for analgesic (57%). The induction agent widely used was ketamine (34), while the maintenance agent was isoflurane in dogs (43.5%) and ketamine in cats (37.3%). The anesthesia monitoring tools that are widely used were thermometers (89.6%) and pulse oximeters (38.8%). As conclusion, the majority of respondents were considered to have understood anesthesia management in accordance with recommendations, however, this understanding could be improved through continuing education.